Inventory Control to Reduce Costs - Muhammad Bayu (International Forum of Researchers and Lecturers, 2025)
In facing fluctuations in the demand for spare parts at PT. SUN STAR MOTOR SURABAYA to avoid shortages that could disrupt its business operations, the company must ensure it can meet customer demands for specific items or orders. This means the company will lose an opportunity to earn profits. Before applying Safety Stock, Reorder Point, Economic Order Quantity, Maximum Inventory, and Total Inventory Cost, the company frequently faced spare parts stock shortages. To solve this issue, Safety Stock, Reorder Point, Economic Order Quantity, Maximum Inventory, and Total Inventory Cost are applied to determine order quantity, order time, and inventory levels for reordering. The results from inventory calculations can help determine the optimal spare parts needs for the company.